Nemesis - Nesbø, Jo, 1960- (Nesbø, Jo, 1960- Harry Hole series., 2017)
Oslo Police Detective Harry Hole is assigned to investigate a series of bank robberies of unparalleled savagery while at the same time absolving himself of the murder of his former girlfriend in a criminal investigation led by his longtime adversary Tom Waaler and Waaler's vigilante police force.